ANALISIS SUMBER DAN PERUBAHAN ANGGARAN PADA BADAN PENGELOLA KEUANGAN DAERAH (BPKD) PROVINSI SULAWESI SELATAN - nasrullah nasrullah; Abdul Muttalib; Hasdiati Latif (Jurnal Ilmu Manajemen Profitability, 2020)
This study aims to determine the Analysis of Sources and Budget Changes at the Regional Finance Management Agency (BPKD) of South Sulawesi Province. This type of research is a quantitative descriptive approach, the data processed are budget changes in the Regional Financial Management Agency of South Sulawesi Province 2016 to 2018. The data analysis technique used in the study uses measurement of effectiveness on budget changes. Based on the calculation result in 2016 of 77%, in 2017 of 56% and in 2018 of 82%.